2019
DOI: 10.3390/pharmacy7010011
|View full text |Cite
|
Sign up to set email alerts
|

Readiness of Pharmacists Based in Utah About Pain Management and Opioid Dispensing

Abstract: Prescription opioid use disorder is a growing epidemic and pharmacists as the dispensers of prescription drugs can play a crucial role in the management of the opioid crisis. However, few studies have examined pharmacists’ perceptions of their role in it. The objective of this study was to evaluate the perceptions of pharmacists in Utah regarding their role in the opioid epidemic. The study utilized a cross sectional online survey design to understand the pharmacist knowledge and beliefs regarding pain managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…Only half of the respondents felt that pharmacists should educate physicians about opioid pharmacotherapy or establishing a collaborative practice agreement. 64 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only half of the respondents felt that pharmacists should educate physicians about opioid pharmacotherapy or establishing a collaborative practice agreement. 64 …”
Section: Resultsmentioning
confidence: 99%
“…63 A survey of Utah pharmacists investigated the pharmacists' perceptions towards topics such as opioids, pain management, and naloxone. 64 Pharmacists held positive attitudes toward dispensing naloxone to patients at high risk for opioid overdose or a third party of those at high risk for opioid abuse. Pharmacists should educate and counsel patients on the risk of addiction with regard to use or extended duration of opioids, and the signs and symptoms of an opioid overdose.…”
Section: Pharmacist Behaviors and Attitudesmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5] Certain medications like opioids need to be dispensed only under pharmacist supervision. 6 However, medication counseling may be often declined by the patients. 3,7 Understanding the role of pharmacists and technicians in the patient counseling process is thus necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Due to these factors, namely relatively easy access to patients and extensive drug and healthcare knowledge, the implementation of practical screening tools in community pharmacies may be an effective strategy to identify patients who exhibit problematic opioid use. However, previous research that has studied pharmacist interest and ability to identify and engage patients regarding opioid use has shown that while most pharmacists view problematic use as a major concern, they report lack both the tools and training to effectively do so 27,28…”
Section: Introductionmentioning
confidence: 99%